The stellate plan of the Garbhagriha of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The stellate plan of the garbhagriha (sanctum sanctorum) of the Undeshwar Temple makes this distinct from the other two temples of the Bijolia temple complex. The beauty of this stellate temple is further enhanced by the carving of the base mouldings which consist of bhittas, karnika, kapotapalika, grassapatta, gajathara, Kumbha and Kalasha.